Temas avanzados de análisis por elementos finitos - Zienkiewicz, O.C.; Gallagher, R.H; Marcal, P.V. (My University, 1976)
We shall see how with a broad definition, the finite difference techniques fall into a “sub-class” of the general finite element methodology wich indeed embraces many other classical approximation procedures.
Keywords: mecánica estructural; análisis; hibridas; métodos; flujo viscoso; ambiental